Inequities in incidence, morbidity and expenditures on prevention and treatment of malaria in southeast Nigeria - Uzochukwu Benjamin S; Onwujekwe Obinna E; Uguru Nkolika P; Igiliegbe Godwin C; Eze Soludo B (BMC, 2009)
Abstract Background Malaria places a great burden on households, but the extent to which this is tilted against the poor is unclear. However, the knowledge of the level of the burden of malaria amongst different population groups is vital for ensuring equitable control of malaria. This paper examined the inequities in occurrence, economic burden, prevention and treatment of malaria. Methods The study was undertaken in four malaria endemic villages in Enugu state, southeast Nigeria. Data was collected using interviewer-administered questionnaires. An asset-based index was used to categorize the households into socio-economic status (SES) quartiles: least poor; poor; very poor; and most poor. Chi-square analysis was used to determine the statistical significance of the SES differences in incidence, length of illness, ownership of treated nets, expenditures on treatment and prevention. Results All the SES quartiles had equal exposure to malaria. The pattern of health seeking for all the SES groups was almost similar, but in one of the villages the most poor, very poor and poor significantly used the services of patent medicine vendors and the least poor visited hospitals. The cost of treating malaria was similar across the SES quartiles. The average expenditure to treat an episode of malaria ranged from as low as 131 Naira ($1.09) to as high as 348 Naira ($2.9), while the transportation expenditure to receive treatment ranged from 26 Naira to 46 Naira (both less than $1). The level of expenditure to prevent malaria was low in the four villages, with less than 5% owning untreated nets and 10.4% with insecticide treated nets. Conclusion Malaria constitutes a burden to all SES groups, though the poorer socio-economic groups were more affected, because a greater proportion of their financial resources compared to their income are spent on treating the disease. The expenditures to treat malaria by the poorest households could lead to catastrophic health expenditures. Effective pro-payment health financing and health delivery methods for the treatment and prevention of malaria are needed to decrease the burden of the disease to the most-poor people.